Origin of the Campinaranas and Ecological Resilience Patterns: Analysis in Silves-Amazonas - Brazil - de Abreu, Nadia Rafaela; Reis, Eusébio Joaquim Marques dos; Vieira, Antonio Fábio Sabbá Guimarães (Sociedade & Natureza, 2024)
The research addresses the origin of the Campinaranas and the primary characteristics of this Amazonian landscape. The results presented herein are part of a doctoral thesis entitled: The Relationship between the Campinaranas Forests and the Ecological Resilience Process (Amazon, Brazil). The Campinaranas are atypical landscapes in the Amazon, dispersed in the Dense Ombrophilous Forest. They have sandy soils and small-scale vegetation. Various methodological procedures were used to evidence the Campinaranas' origin, based on field research, in which five sample collection points were selected in the Sanabani river basin in Silves, Amazonas - Brazil. These samples enabled an understanding of the main particularities of the Campinaranas (soil, vegetation, and human interventions) through soil analysis (soil chemistry and physics), comparative analysis, a vegetation inventory, and classification of the environment. The main objectives were: 1) To quantify the soil and vegetation variables of the Campinaranas in the study area; 2) To identify the fundamental interventions in the Campinaranas areas and the origin of this environmental system. The results demonstrate that the Campinaranas are diverse environments resulting from the forest's ecological resilience after an intervention event. The analyses verify that environmental changes modify the soil granulometry and, consequently, the entire ensuing structure.